Breaking inversion symmetry by protonation: experimental and theoretical NEXAFS study of the diazynium ion, N2H+. Issue 32 (4th August 2021) - Couto, Rafael C.; Hua, Weijie; Lindblad, Rebecka; Kjellsson, Ludvig; Sorensen, Stacey L.; Kubin, Markus; Bülow, Christine; Timm, Martin; Zamudio-Bayer, Vicente; von Issendorff, Bernd; Söderström, Johan; Lau, J. Tobias; et al.
Abstract : As an example of symmetry breaking in NEXAFS spectra of protonated species we present a high resolution NEXAFS spectrum of protonated dinitrogen, the diazynium ion N2 H + . Abstract : As an example of symmetry breaking in NEXAFS spectra of protonated species we present a high resolution NEXAFS spectrum of protonated dinitrogen, the diazynium ion N2 H + . By ab initio calculations we show that the spectrum consists of a superposition of two nitrogen 1s absorption spectra, each including a π* band, and a nitrogen 1s to H + charge transfer band followed by a weak irregular progression of high energy excitations. Calculations also show that, as an effect of symmetry breaking by protonation, the π* transitions are separated by 0.23 eV, only slightly exceeding the difference in the corresponding dark (symmetry forbidden) and bright (symmetry allowed) core excitations of neutral N2 . By DFT and calculations and vibrational analysis, the complex π* excitation band of N2 H + is understood as due to the superposition of the significantly different vibrational progressions of excitations from terminal and central nitrogen atoms, both leading to bent final state geometries. We also show computationally that the electronic structure of the charge transfer excitation smoothly depends on the nitrogen–proton distance and that there is a clear extension of the spectra going from infinity to close nitrogen–proton distance where fine structures show some, although not fully detailed, similarities. An interesting feature of partial localization of the nitrogen core orbitals, with a strong, non-monotonous, variation with nitrogen–proton distance could be highlighted. Specific effects could be unraveled when comparing molecular cation NEXAFS spectra, as represented by recently recorded spectra of N2 + and CO +, and spectra of protonated molecules as represented here by the N2 H + ion. Both types containing rich physical effects not represented in NEXAFS of neutral molecules because of the positive charge, whereas protonation also breaks the symmetry. The effect of the protonation on dinitrogen can be separated in charge, which extends the high-energy part of the spectrum, and symmetry-breaking, which is most clearly seen in the low-energy π* transition.